2010
DOI: 10.2478/v10019-010-0026-8
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic imaging of traumatic pseudoaneurysm of the thoracic aorta

Abstract: BackgroundThe purpose of the study was the presentation of findings and diagnostic imaging in patients with traumatic pseudoaneurysms of the thoracic aorta, as a rare consequence of road traffic accidents.Patients and methodsIn 22 years we have found 8 traumatic pseudoaneurysms of the thoracic aorta, out of which 7 (87.5%) in male and 1 (12.5%) in female patients. At the time of accidents the youngest patient was 21 and the oldest was 55 (mean age 33.8 years), and at the moment of diagnosing a pseudoaneurysm t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…A blunt trauma can damage the thoracic aorta by several mechanisms (e.g., fracture dislocating thoracic vertebras; penetration of the first rib and clavicle), but the majority occurs after significant decelerating traumas, so that some authors believe that all victims of decelerating traumas, such as motor vehicle crashes, should be referred to an angiographic examination of the aorta [ 30 ].…”
Section: Mediastinal Traumamentioning
confidence: 99%
“…A blunt trauma can damage the thoracic aorta by several mechanisms (e.g., fracture dislocating thoracic vertebras; penetration of the first rib and clavicle), but the majority occurs after significant decelerating traumas, so that some authors believe that all victims of decelerating traumas, such as motor vehicle crashes, should be referred to an angiographic examination of the aorta [ 30 ].…”
Section: Mediastinal Traumamentioning
confidence: 99%
“…TOF MRA provides information on vessel conformation and functional information, and allows high definition images of blood vessels within a relatively short time. These attributes have spurred its popularity [10][11][12][13]. TOF MRA produces a low signal by saturating the signal from a stationary object, and uses blood flow to yield a contrast difference between stationary anatomical objects and blood vessels [13].…”
Section: Discussionmentioning
confidence: 99%
“…There are just a few articles that deal with that issue, e.g. [ 1 ]. In traumatized patients, the authors in [ 2 ] found aortic injuries with an incidence of about 22 per 100,000 per annum.…”
Section: Introductionmentioning
confidence: 99%